A reflectionless compact elliptical half Maxwell fish-eye lens designed by transformation optics - Eskandari, Hossein (Frontiers in Materials, 2022)
A two-dimensional half Maxwell fish-eye lens is compressed using a linear transformation that maps a half circle to a half ellipse. The focusing property of the lens is preserved while making the device more compact. Boundary reflections are investigated for both TE and TM polarizations. Reflections are suppressed for the beam directed toward the optical axis of the lens. A designed prototype is shown to provide a scanning range of +-20 degrees with negligible reflections. Utilizing COMSOL Multiphysics, the design’s functioning is verified.